Fragrant orchids (multimedia) - Tan, Agnes Shek Li .
Fragrance is a bons to the beautiful orchids.Everything about the orchids is different and perhaps fascinating.All the interesting information such as the composition of fragrant orchids, how and when the scent being produced,the variety fragrances of orchids,transmitting scent in hybridzing will be include in the multimedia module.Beside that,there are information on fragrant and pollination,fragrant orchid in commerce and Malayan species of fragrant orchids in the module.Macromedia Authoware is the main authoring tool to construct the module.The multimedia module combines all the elements the elements of multimedia in order to make the module more interesting.This multimedia module is a powerful tool for outstanding learning process.With this multimedia module,the users can widen their knowledge on fragrant orchids.